Cell Death Induction and Protection by Activation of Ubiquitously Expressed Anion/Cation Channels. Part 2: Functional and Molecular Properties of ASOR/PAC Channels and Their Roles in Cell Volume Dysregulation and Acidotoxic Cell Death - Okada, Yasunobu; Sato-Numata, Kaori; Sabirov, Ravshan Z.; Numata, Tomohiro (Frontiers in Cell and Developmental Biology, 2021)
For survival and functions of animal cells, cell volume regulation (CVR) is essential. Major hallmarks of necrotic and apoptotic cell death are persistent cell swelling and shrinkage, and thus they are termed the necrotic volume increase (NVI) and the apoptotic volume decrease (AVD), respectively. A number of ubiquitously expressed anion and cation channels play essential roles not only in CVR but also in cell death induction. This series of review articles address the question how cell death is induced or protected with using ubiquitously expressed ion channels such as swelling-activated anion channels, acid-activated anion channels, and several types of TRP cation channels including TRPM2 and TRPM7. In the Part 1, we described the roles of swelling-activated VSOR/VRAC anion channels. Here, the Part 2 focuses on the roles of the acid-sensitive outwardly rectifying anion channel (ASOR), also called the proton-activated anion channel (PAC), which is activated by extracellular protons in a manner sharply dependent on ambient temperature. First, we summarize phenotypical properties, the molecular identity, and the three-dimensional structure of ASOR/PAC. Second, we highlight the unique roles of ASOR/PAC in CVR dysfunction and in the induction of or protection from acidotoxic cell death under acidosis and ischemic conditions.